The Use of Intelligent Decision Support System in Traveloka Company's Decision-Making Process - Aprizanti, Dea; Norbaida, Norbaida; Arini, Siti; Sumarni, Titin (Nomico, 2024)
The aviation industry is currently experiencing rapid growth due to advancements in information technology, which have transformed the way consumers search for information and book tickets online. Traveloka, founded in March 2012, is one of the companies that has successfully leveraged this technology optimally. With intelligent algorithms, Traveloka can analyze user preferences and provide suitable recommendations, although the effectiveness of its intelligent support system needs further investigation to enhance user satisfaction and operational efficiency. This study aims to evaluate the effectiveness of Traveloka's intelligent support system in decision-making, using qualitative methods and a literature review approach. The development model proposed by Peter Fenrich is used to ensure that the system built can effectively and efficiently meet user needs. The research results show that Traveloka's intelligent support system is very helpful in providing accurate recommendations, increasing user satisfaction and operational efficiency, and providing a competitive advantage in the e-commerce market. Overall, the use of information technology and intelligent support systems at Traveloka significantly contributes to the advancement of the aviation industry, simplifies the ticket booking process, and enhances the company's competitiveness. Further research is needed to continue improving the effectiveness and efficiency of this system, thereby providing greater benefits for consumers and the company.